PUBLIC-PRIVATE PARTNERSHIP IN THE EAEU TRANSIT ECONOMY: RUSSIA AND CENTRAL ASIA STATES - E. V. Pak (Vestnik MGIMO-Universiteta)
Book Review. Zoidov, K., Medkov, A., Zoidov, Z. “Public-Private Partnership – The Basis of Innovative Development and Security in The Transit Economy” / Foreword and ed. by V. Tsvetkov. Moscow: Economic Education Publishing House, 2017, 528 p. (In Russian)The book under review is a collective monograph of authors representing Market Economy Institute of Russian Academy of Sciences. The monograph applies quantitative methods of analysis to capture current problems and prospects of building transit economy in Russia and Central Asian states on the public-private partnership basis.